A natural disaster student support program for online students faces the challenge of COVID‐19. Issue 176 (28th February 2022) - Sanders, Jennie; Howlett, Bernadette; Jungbauer, Michelle; Koch, Alonna; Bliven, AnnaMaria; Velarde, Jesse; Saulnier, Heather
Abstract: This article describes Western Governors University's emergency management student support program in place prior to the pandemic and the challenge to adapt and address the unprecedented needs students faced due to COVID‐19. Included are key lessons learned in addressing the impact of COVID‐19 and evidence‐based learnings in response to the large‐scale student needs during the prolonged pandemic.